APPLICATION OF IT TOOLS IN MANAGING SMALL AND MEDIUM-SIZED ENTERPRISES IN THE CONTEXT OF CREATING ENTREPRENEURIAL ORIENTATION - Renata Lisowska (Acta Scientiarum Polonorum. Oeconomia, 2018)
The presence of small and medium-sized enterprises on the Internet in the era of increasing global competition has become a necessity. These entities have begun to notice the benefits that can be obtained by using modern IT tools in various areas of their operations. The aim of the paper is to analyse and evaluate the impact of the use of IT tools in various areas of SMEs’ operations on creating their entrepreneurial orientation. The implementation of such a goal required, on the one hand, a literature review and an analysis of current research on the IT tools used by small and medium-sized enterprises in the context of creating their entrepreneurial orientation, and on the other hand, conducting the author’s own research among small companies. Quantitative research was carried out from December 2017 to January 2018 among 400 small enterprises in Poland by means of a survey questionnaire using the CATI technique.